Pembuatan tortila jagung (Zea mays L) dari substitusi tepung ampas tahu dan tepung jagung dengan penambahan natrium bikarbonat - Muhammad Said Siregar; Lismadayanti Lismadayanti; Desi Ardilla (AGROINTEK, 2023)
This study aims to determine the effect of the substitution of tofu flour and corn flour by the addition of sodium bicarbonate in a completely randomized design with two replicates. The first factor is the substitution of tofu flour: corn flour (S) are: S1=100:0, S2=25:75, S3=50:50, S4=75:25, and  S5=0:100. The second factor is the effect of adding sodium bicarbonate (P), which consists of three levels, namely: P1=0.00 %, P2=0.20 %, and P3=0.30 %. The observed parameters: protein content, water content, fat content, ash content, and organoleptic texture, color, and flavor. The statistical analysis showed that the substitution of tofu flour: with corn flour provides a highly significant effect (P0.05) on the protein content, water content, fat content, ash content, organoleptic color, flavor, and texture. The effect adding sodium bicarbonate provides a highly significant effect (P0.05) on the protein content, moisture content, fat content, ash content, and organoleptic texture and no significant effect on organoleptic taste and color.